Utopia lost : the United Nations and world order - Righter, Rosemary (New York : Twentieth Century Fund Press, 1995)
Rosemary Righter examines the UN's future place in a world of tumultuous political and technological change, presenting an anatomy of the complex tangle of global organizations that has evolved since 1946, and of their struggle to adapt. She argues that the ideals and cooperative purposes the UN stands for retain their resonance, and that powerful governments are now readier, in principle, to turn to it. But they will continue to do so only where, and if, it matches the needs of a new and more active era of multilateral diplomacy. Righter examines every aspect of the UN: the hopes and contradictions built into its Charter, the unreality which has come to permeate what passes for debate there, the legacy of ideological confrontation, and the tides of reforming zeal that, almost since its inception, have washed over it and left almost no trace.
Foreword / Richard C. Leone -- pt. I. The Layout of the Labyrinth. 1. Utopia Invented. 2. Boxes of Tricks: The UN Machine. 3. The Politics of Illusion -- pt. II. The Webs of Ideology. 4. "New Orders": The Politics of Confrontation. 5. The Western Dilemma -- pt. III. From Reform to Revolt. 6. Tinkering with Utopia. 7. Multilateralism for the Marketplace. 8. The Challenge from Washington -- pt. IV. Beyond Utopia. 9. Ways Ahead: The Options. 10. The Discriminating Buyer's UN. 11. Another "New World Order"? 12. An Improbable Phoenix.
"A Twentieth Century Fund book."
Includes bibliographical references (pages 377-399) and index.
Keywords: United Nations; Nations Unies; United Nations; International organization; Organisation internationale; 89.72 international organizations; Relations internationales; 2; International organization; Verenigde Naties; Internationale orde; Book